2017
DOI: 10.1021/acs.analchem.7b02499
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Selective Detection of Fe3+ Based on Graphene Quantum Dots as Fluorescent Probes: The Ksp of a Metal Hydroxide-Assisted Mechanism

Abstract: Graphene quantum dots (GQDs) have been widely used as fluorescence probes to detect metal ions with satisfactory selectivity. However, the diverse chemical structures of GQDs lead to selectivity for multiple metal ions, and this can lead to trouble in the interpretation of selectivity due to the lack of an in depth and systematic analysis. Herein, bare GQDs were synthesized by oxidizing carbon black with nitric acid and used as fluorescent probes to detect metal ions. We found that the specific ability of GQDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(81 citation statements)
references
References 26 publications
3
78
0
Order By: Relevance
“…However, the increasing pH value showed the interference from other ions and selectivity for Fe 3+ , which was quite low at pH 1.4. Moreover, this study showed similar results in terms of quenching performed by Fe 3+ [ 141 ].…”
Section: Bio-imaging Applications Of Gqdssupporting
confidence: 81%
“…However, the increasing pH value showed the interference from other ions and selectivity for Fe 3+ , which was quite low at pH 1.4. Moreover, this study showed similar results in terms of quenching performed by Fe 3+ [ 141 ].…”
Section: Bio-imaging Applications Of Gqdssupporting
confidence: 81%
“…Some reports have shown that the good affinity between quencher cations and functional groups on the surface of quantum dots relates to the good selectivity of GQDs’ fluorescence probe [47,48,49]. XPS and FTIR analysis show that there are many carboxyl, hydroxyl, amino, and hydrosulfonyl groups on the surface of N, S-GQDs.…”
Section: Resultsmentioning
confidence: 99%
“…For each ion, sensing has been reported through a variation in GQD fluorescence due to a quenching mechanism. The quenching of GQD fluorescence by dissolved ions has been attributed to both the formation of GQD‐ion complexes, resulting in non‐radiative electron transfer from the GQD excited state to the ion, and to disruption of the surface passivation of the GQD, which decreases the GQDs photoluminescent quantum yield …”
Section: Introductionmentioning
confidence: 99%